Exploring alternative protein sources: Evidence from patents and articles focusing on food markets. (15th November 2022) - Otero, Deborah Murowaniecki; da Rocha Lemos Mendes, Gabriela; da Silva Lucas, Andressa Jantzen; Christ-Ribeiro, Anelise; Ribeiro, Camila Duarte Ferreira
Highlights: This study shows the alternative protein source (APS) analysis of articles and patents. Understanding APS in the articles and patents is relevant to develop new technologies. The food industry area had the highest number of filed patents. The market has shown different food applications for APS. This study can help companies and researchers to develop new APS technologies. Abstract: This review considers alternative protein sources through the analysis of food science literature and patents. Data collection was performed from scientific literature and patent documents using the Scopus and National Institute of Industrial Property databases, with a term combination "alternative protein source" and "source* AND protein* AND alternative*". A total of 945 documents were analyzed. The scientific prospection showed that agricultural and biological science was the main application area. The food industry area had the highest number of filed patents. The annual evaluation of published documents demonstrated that this area had been investigated since the 1970s, and the number of articles was twice than that of filled patents. Although protein products are available for sale, animal and vegetable sources replace conventional protein products. Presently, alternative protein sources are already a worldwide trend in the food industry, enabling the development of new products to facilitate their insertion into the consumer market.